THE EFFECT OF EXTRINSIC, INTRINSIC REWARDS AND WORK FLEXIBILITY ON JOB SATISFACTION FOR MILLENNILAS GENERATION (CASE STUDY ON PROPERTY AGENT IN SURABAYA) - Crysilia Lisa; Praptini Yulianti (Universitas Mercu Buana, 2021)
This study aims to determine the effect of extrinsic, intrinsic rewards and work flexibility of job satisfaction for millennial generations especially work as a property agents. Types of research used in this study is a quantitative and research methods are used methods of explanation. Samples taken as many as 50 property agents by using purposive sampling. Analysis techniques used are descriptive statistics and multiple linear regression analysis. The Result of this study indicate intrinsic rewards and work flexibility has positive and significant effect on job satisfaction through millennials generation work as a agent property rather that extrinsic reward.